Umm Salamah's Compassion: Bridging Orphan Welfare From Battlefield To Modern Law - Binte Mahfuh, Siti Khadijah; Ariffin, Tajul; Kosasih, Engkos (Universitas Islam Negeri Sumatera Utara, 2024)
This article, titled